Scoping Review: Pengaruh Latihan Fisik terhadap Perbaikan Gejala Klinis Osteoarthritis - Navira Salsabila Putri; Abdul Hadi Hassan; Meike Rachmawati (UNISBA Press, 2022)
Abstract. Clinical symptoms of OA consist of pain, morning stiffness, joint tenderness, swelling, crepitus, restriction, joint displacement, and bone enlargement. These clinical symptoms affect the quality of life, function, and psychological parameters. OA management consists of pharmacological therapy and non-pharmacological therapy. Non-pharmacological interventions are an inseparable part of OA therapy planning. One of the non-pharmacological therapies is physical exercise. Physical exercise can build muscle strength and endurance, increase flexibility and joint movement, increase aerobic activity, and increase joint mobility in OA. The purpose of this study was to find out what physical exercise can affect the improvement of clinical symptoms of OA. The research was conducted using the Scoping Review method on scientific articles taken from 3 databases, namely PubMed, ScienceDirect, and springer link for analysis, identification, and evaluation. The initial search results consist of 2,910 articles, then the eligible results consist of nine articles. Of the nine articles, three articles provide strength training interventions. Two articles provide a walking exercise intervention. The other four articles provide physical exercise interventions in the form of aquatic exercises, biomechanics-based yoga exercises, internet-based exercises, and home-based non-weight bearing (NWB) quadriceps exercises. The conclusion of this study based on articles that have been reviewed shows that physical exercises that can be given as OA therapy consist of strength training, walking exercises, aquatic exercises, biomechanics-based yoga exercises, and internet-based physical exercises. All of these physical exercises play a role in improving clinical symptoms of knee OA. Abstrak. Gejala klinis OA terdiri dari nyeri, morning stiffness, tenderness pada sendi, swelling, krepitus, retriksi, perpindahan sendi dan pembesaran tulang. Gejala klinis tersebut memiliki efek pada kualitas hidup, fungsi dan parameter psikologi. Manajemen OA terdiri dari terapi farmakologis dan terapi non farmakologis. Intervensi non farmakologi merupakan bagian yang tidak bisa dipisahkan dalam perencanaan terapi OA. Salah satu terapi non farmakologis adalah latihan fisik. Latihan fisik dapat membangun kekuatan dan daya tahan otot, meningkatkan kelenturan dan gerakan sendi, meningkatkan aktivitas aerobik, dan meningkatkan mobilitas sendi pada OA. Tujuan dari penilitian ini adalah untuk mengetahui latihan fisik apa saja yang dapat memengaruhi perbaikan gejala klinis OA. Penilitian dilakukan dengan metode Scoping Review pada artikel ilmiah yang diambil pada 3 database yaitu PubMed, ScienceDirect, dan springer link untuk dilakukan analasis, identifikasi, dan evaluasi. Hasil pencarian awal terdiri dari 2.910 artikel, kemudian hasil yang eligible terdiri dari sembilan artikel. Dari Sembilan artikel, terdapat tiga artikel yang memberikan intervensi latihan kekuatan. Dua artikel memberikan intervensi latihan berjalan. Empat artikel lainnya meberikan intervensi latihan fisik berupa latihan akuatik, latihan yoga berbasis biomekanik, latihan berbasis internet dan latihan home-based non-weigght bearing (NWB) quadriceps. Kesimpulan dari penelitian ini berdasarkan artikel yang telah dikaji menunjukkan bahwa latihan fisik yang dapat diberikan sebagai terapi OA terdiri dari latihan kekuatan, latihan berjalan, latihan akuatik, latihan yoga berbasis biomekanik, dan latih fisik berbasis internet. Semua latihan fisik tersebut berperan dalam perbaikan gejala klinis OA lutut.